PENINGKATAN HASIL BELAJAR MATEMATIKA PADA MATERI PECAHAN SEDERHANA DENGAN BERBANTUAN MEDIA PUZZLE DIKELAS III SD INPRES AISIO KABUPATEN TIMOR TENGAN SELATAN - Nubatonis, Ledyani; Henukh, Riky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Thesis by Ledyani Nubatonis. PGSD 2019 with the title "Using Puzzle Media in Simple Fractions to Improve Student Learning Outcomes for Class III SD Inpres Aisio, Timor Tengah Selatan Regency". Advisor I Dr. Damianus dao samo, M.Pd and supervisor II Adam Benu, S.Pd, M.Pd. Background This research was conducted because the third grade students of SD Inpres Aisio were taught not to use learning media but the teacher taught the students by the lecture method, so that most of the students looked bored, not enthusiastic in participating in mathematics learning at that time so that after the test was carried out at the end of the lesson most of the students who did not complete or did not achieve the KKM score. The formulation of the research problem is: How is the use of puzzle media in simple fractions to improve the learning outcomes of third grade students of SD Inpres Aisio? This study aims to improve the learning outcomes of third grade students of SD Inpres Aisio on simple fractions through the use of puzzle media. This type of research is Classroom Action Research with the following stages: planning, implementation, observation and reflection. The subjects of this study were 25 grade III students and researchers. Data was collected by means of observation and test techniques. The collected data was processed and further analyzed using qualitative descriptive analysis techniques. The results of the research in the first cycle the average grade of 54.8 increased to 76 in the second cycle, with an increase from the first cycle to the second cycle of 21.2. The percentage of classical learning completeness in the first cycle of 40% increased to 88% in the second cycle, with an increase in the percentage of 48%. Student activity in the first cycle was 64.31 to 82.39 in the second cycle with an increase of 18.08, it can be concluded that the use of puzzle media in simple fractions material can improve student learning outcomes in class III SD Inpres Aisio.